Pelatihan Bahasa Inggris (Part of Speech) Bagi Mahasiswa Ikor FIK UNM - Risan, Rahmad; Rahman, Abdul; G, Hasriani; Nasta, Mardiyanah; Aziz, Asriati (Universitas Negeri Makassar, 2022)
The focus of this workshop is to increase the interest in learning English for students in understanding and identifying the use of part of speech. The participants are the students in the Sports Science Study Program, Faculty of Sports Science, State University of Makassar. The problem of participants is the students’ difficulty in understanding the use of Part of Speech in using English words or sentences both verbally and in writing. The approach used in this workshop consists of three steps which are presenting materials, giving exercises, and giving online and offline,quizzes. Based on the evaluation results, each assignment given to the participants has a significant impact on their knowledge and understanding of the functions and identification of Part of Speech, especially in giving examples of sentences in English. Participants who still had errors in using or identifying some English vocabularies could finally show their enthusiasm in understanding the material by asking a lot of questions to practitioner team. The results achieved in this workshop are (1) participants understand the Part of Speech both in identifying and using them in sentences, (2) the participants are able to make English sentences based on Part of Speech correctly orally or in writing.